longhaul123 wrote:

I have a doubt in Option E

So P+894= 893*78+894 = (893*78)+ (893+1)=893(78+1)=893*79

Im sure that there is some mistake with the method that i followed above but Im not understanding where am i going wrong because if you back solve from the above method 893(78+1)=893*78+893. Can someone help ?

There's a problem where you get

893(78+1)=893*79You are correct to say that P+894= 893*78+894 = (893*78)+ (893+1)

However, the next step cannot be the one you took

You are treating (893+1) as though it were (893*1)

Notice that

if we have (893*78)+ (893*1), then we can factor out the 893 to get: (893*78)+ (893*1) = 893(78 + 1)

However, If we have (893*78) + (893

+1), we cannot factor out the 893 (as I did above)

Does that help?

Cheers,

Brent

_________________

Brent Hanneson – Founder of gmatprepnow.com